Loot : how to steal a fortune - Watson, Jude. (New York : Scholastic Press, 2014)
"When Alfie McQuinn, the notorious jewel thief, is killed on a job, his last words to his son, March, are to "find jewels" and this instruction leads the boy to Jules, the twin sister he never knew he had--and the perfect partner to carry on the family business"--Provided by publisher.
School Library Journal, May 2014.
Pub Weekly, May 2014.
Kirkus Starred, May 2014.
Booklist, June 2014.
Horn Book, October 2014.
Bulletin (Center for Children's books), July 2014.
Keywords: Jewel thieves -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Robbers and outlaws -- Fiction; Jewelry -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Adventure and adventurers -- Fiction; Thieves -- Fiction; Jewelry -- Fiction; Twins -- Fiction; Siblings -- Fiction; Orphans -- Fiction; Adventure fiction; Jewel thieves -- Fiction; Robbers and outlaws -- Fiction; Jewelry -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction